A Library of Rare Earth Oxide Ultrathin Nanowires with Polymer‐Like Behaviors. Issue 45 (7th October 2022) - Fu, Hao; Xu, Yingzhuang; Qiu, Di; Ma, Tengfei; Yue, Guanglu; Zeng, Zhichao; Song, Lianpeng; Wang, Siyuan; Zhang, Shuai; Du, Yaping; Yan, Chun‐Hua
Abstract: Ultrathin nanowires (NWs) have always attracted the attention of researchers due to their unique properties, but their facile synthesis is still a great challenge. Herein we developed a general method for the synthesis of rare earth (RE) oxide ultrathin NWs at atmospheric pressure and low temperature (50 °C). The formation mechanism of ultrathin NWs lies in two aspects: thermodynamic advantage of one dimensional (1D) growth at low temperature, and supplement of effective monomers. As an extension, fifteen kinds of RE oxide ultrathin NWs were synthesized through this strategy, and they all exhibited polymer‐like behaviors. Meanwhile, the high viscosity, organic gel, wet‐ and electro‐spinning of Ce‐Mo‐O NWs were studied in detail, demonstrating the similarity of ultrathin inorganic NWs to polymers. In addition, the Ce‐Mo‐O ultrathin NWs were used as photocatalysts for toluene oxidation and showed excellent performance with toluene conversion ratio of 83.8 %, suggesting their potential application in organic photocatalysis. Abstract : A general and facile colloidal method to synthesize ultrathin nanowires at atmospheric pressure and low temperature (50 °C) is developed. The mechanism of nanocrystal growth along different dimensions is discussed. Fifteen kinds of RE‐Mo‐O (RE=Y, La‐Nd, and Sm‐Lu) ultrathin nanowires could be synthesized using this method. All of them exhibited polymer‐like behavior.